2005
DOI: 10.1111/j.1572-0241.2005.41168.x
|View full text |Cite
|
Sign up to set email alerts
|

A1166C Angiotensin II Type 1 Receptor Gene Polymorphism May Predict Hemodynamic Response to Losartan in Patients with Cirrhosis and Portal Hypertension

Abstract: These results suggest that there is a relationship between the AT1R A1166C polymorphisms and the therapeutic response to losartan. The genetic testing may be used as a predictive factor of this response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…Indeed, in the three trials from which our major conclusions were drawn, the heterogeneity was statistically insignificant when separated by Child Pugh class using individual patient data. The potential contribution of genetic variation in AT1 receptors on heterogeneity could not be evaluated as this was not tested in any of the included studies [23]. Lastly, as with all meta-analyses, this analysis is also limited by the quality of the studies entered into it.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, in the three trials from which our major conclusions were drawn, the heterogeneity was statistically insignificant when separated by Child Pugh class using individual patient data. The potential contribution of genetic variation in AT1 receptors on heterogeneity could not be evaluated as this was not tested in any of the included studies [23]. Lastly, as with all meta-analyses, this analysis is also limited by the quality of the studies entered into it.…”
Section: Discussionmentioning
confidence: 94%
“…The full-text of 40 of these potentially relevant articles was reviewed independently. Twenty-two articles were excluded due to the lack of a control group (8/22) [18][19][20][21][22][23][24][25], the lack of HVPG measurements (12/22) [9,[26][27][28][29][30][31][32][33][34][35][36], or because they were review articles (2/22) [37,38] Fig. 1.…”
Section: Searchmentioning
confidence: 99%
“…For instance, Sethupathy and coworkers [31] observed that a target site for the hsa-miR-155, within the 3′ UTR of the human AGTR1 gene that contains the SNP rs5186 (also known as A1166C), leads to allele-specific underexpression of AGTR1, suggesting that the abrogation of miR-155 binding elevates the mRNA-AGTR1 levels. Interestingly, abundant data provide strong evidence of an association of the A1166C variant and cardiovascular disease, including hypertension, and therapeutic response to losartan [32].…”
Section: The Role Of Polymorphisms At Microrna Target Sites In the Pamentioning
confidence: 99%
“…The SNPs studied are intronic, but they may affect transcriptional activity or possibly be in linkage disequilibrium with functional coding variants. It is also possible the AGTR1 SNPs may affect response to treatment with blockers; there is a relationship between rs5182 and therapeutic response to the angiotensin II receptor antagonist losartan in patients with cirrhosis and portal hypertension ( 285 ).…”
Section: Agtr1mentioning
confidence: 99%